2010
DOI: 10.1016/j.socscimed.2010.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Narratives that address affective forecasting errors reduce perceived barriers to colorectal cancer screening

Abstract: Narratives from similar others may be an effective way to increase important health behaviors. In this study, we used a narrative intervention to promote colorectal cancer screening. Researchers have suggested that people may overestimate barriers to colorectal cancer screening. We recruited participants from the US, ages 49–60 who had never previously been screened for colorectal cancer, to read an educational message about screening for the disease. One-half of participants were randomly assigned to also rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 39 publications
1
126
2
2
Order By: Relevance
“…162,172,174,[176][177][178] An introductory question was asked to encourage or remind the participant to read the information material sent to them prior to beginning the questionnaire: 'Have you read the orange booklet, "Bowel Cancer Screening: The Facts" found inside the NHS envelope?'. The intervention group were also asked the same question in relation to the narrative leaflet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…162,172,174,[176][177][178] An introductory question was asked to encourage or remind the participant to read the information material sent to them prior to beginning the questionnaire: 'Have you read the orange booklet, "Bowel Cancer Screening: The Facts" found inside the NHS envelope?'. The intervention group were also asked the same question in relation to the narrative leaflet.…”
Section: Methodsmentioning
confidence: 99%
“…Presenting information in a narrative format is becoming a popular form of health communication and has shown encouraging results in the science literature. 156,158 Dillard et al 162 found that by integrating a short narrative to non-narrative factual information, the anticipated impact of barriers to screening (via colonoscopy) was reduced, while perceived personal risk and intention to have a colonoscopy were enhanced. 162 The inclusion of a bowel cancer screening narrative has also been found to increase colonoscopy attendance fourfold when compared with providing non-narrative information only.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the use of stories as a means to behavioural change remains an emerging innovation, the limited existing research is encouraging. For example, intervention groups exposed to informative and persuasive personal narratives have demonstrated increased intentions to quit smoking [46] and reduced perception of barriers to cancer screening [47]. Critically, neither "increased intentions" nor "reduced perceptions of barriers" constitute the Holy Grail of behavioural change, albeit they are useful predictors.…”
Section: Jack Greg and Martinmentioning
confidence: 99%